Penerapan Program Membaca Al-Qur’an dalam Penguatan Karakter Religius Dimensi Beriman dan Bertakwa di SDN 82 Kota Bengkulu - Sinar Khomalasari; Eka Wulandari; Dwi Indah Lutfiatin; Enjel Pratiwi (Yayasan Darusssalam Bengkulu, 2024)
Religious character education at SD Negeri 82 Bengkulu City is not supported by extracurricular activities or additional hours at school. In order to improve the religious character of students, the Merdeka Curriculum is holding a Al-Qur'an reading program to strengthen the profile of Pancasila students with the dimensions of faith and piety. The aim of this research is to describe the implementation and obstacles of the Al-Qur'an reading program in strengthening the profile of Pancasila students with the faith and piety dimension at SD Negeri 82 Bengkulu City. This type of research is qualitative research. This research method uses descriptive qualitative methods. The research results can be concluded that, 1) the activity program is reading the Al-Qur'an before learning begins and conveying motivation from the class teacher. This program has fulfilled the aspects of the Pancasila student profile, the dimensions of faith and piety, namely religious morals, personal morals, and morals towards fellow human beings. 2) Obstacles in implementing the Al-Qur'an reading program include; Lack of time consistency in implementation, students' varying reading abilities, and lack of teacher ability in mastering the laws of reading the Al-Qur'an.